Influence of Surface Finishes and a Calcium Phosphate-Based Consolidant on the Decay of Sedimentary Building Stones Due to Acid Attack - Molina, E.; Arizzi, A.; Benavente, D.; Cultrone, G. (Frontiers in Materials, 2020)
Natural stone has long been used as a building material because of its physical-mechanical resistance and its aesthetic appeal. However, over the last century increasing industrial activity has created a more polluted, more acidic urban atmosphere that can cause serious damage to many buildings and historic monuments, and in particular those made with carbonate rocks, which are most prone to decay. In order to mitigate these effects, a number of phosphate-based consolidants have been developed. These are applied to the surface of the rock and are highly compatible with the carbonated substrate. Research about the role of the surface and its different possible finishes in the transmission of the agents that damage or protect the stone would therefore be very useful, both when choosing the most suitable stone for new constructions and when restoring historic buildings. The main objective of this research was to determine whether the roughness of three types of surface finish (saw-cut, honed and bush-hammered) influences the durability of four types of natural stone (two calcarenites, one travertine and one sandstone) widely used in Andalusia (Spain). The efficacy of a calcium phosphate-based consolidant as a mitigator of deterioration in polluted urban environments was also studied and to this end the physical properties of non-treated and treated samples were measured and compared. The samples were then exposed to artificial atmospheres with SO2 pollution in order to assess the damage caused to each surface finish. The results indicate that all the surface finishes were vulnerable to the decay caused by acidic atmospheres, although the saw-cut finish was less affected by acid attack, perhaps because it did not require additional industrial processing. The mineral composition and texture of the rocks were critical factors in terms of the amount and type of decay they suffered, and the travertine and sandstone were more resistant to deterioration than the calcarenites. Similarly, the pore system of each rock was decisive in the penetration of the consolidant, so ensuring that the treated samples were more resistant to acid attack without significantly altering the water vapor permeability, the color or the roughness of the surface.